Tropological Thought and Action Essays on the Poetics of Imagination. - Živković, Marko (Studies in Rhetoric and Culture Ser., 2021)
From twilight in the Himalayas to dream worlds in the Serbian state, this book provides a unique collection of anthropological and cross-cultural inquiry into the power of rhetorical tropes and their relevance to the formation and analysis of social thought and action through a series of ethnographic essays offering in-depth studies of the human imagination at work and play around the world.